(untitled) (Al-Academy, 2024)
This research aims to explore the advanced artistic and technical processes involved in the design and production of animation in films and television series, It focuses on analyzing modern tools and techniques used in animation and how they impact production quality and visual storytelling, The study addresses the challenges associated with integrating artistic creativity with advanced technology and how to balance these elements to ensure high-quality artistic outcomes, Through the study and analysis of a sample of contemporary productions, the research highlights how these processes are applied and their effects on the audience.